2021
DOI: 10.1088/1755-1315/944/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Life form, diversity, and spatial distribution of macroalgae in Komodo National Park waters, East Nusa Tenggara

Abstract: Komodo National Park is one of the favorite destinations for both domestic and international marine tourism. Marine tourism activities have caused environmental changes and impact on fisheries and marine resources. Macroalgae were also affected by the environmental changes, so management of macroalgae was required. Ecological data of macroalgae can be used as baseline data for coastal area management. The study aimed to determine the life form, species composition, spatial distribution, and ecological aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Tourism-induced alteration of habitats found in water-related ecosystems is a pressing environmental concern. Tourism activities expanding into coastal areas, wetlands, coral reefs, and other sensitive ecosystems may lead to habitat degradation and loss [ 155 ]. Studies have revealed how infrastructure development, pollution from tourism activities, and physical disturbances due to tourism activities can have adverse impacts on these habitats, altering biodiversity and biocomplexity [ 155 ].…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Tourism-induced alteration of habitats found in water-related ecosystems is a pressing environmental concern. Tourism activities expanding into coastal areas, wetlands, coral reefs, and other sensitive ecosystems may lead to habitat degradation and loss [ 155 ]. Studies have revealed how infrastructure development, pollution from tourism activities, and physical disturbances due to tourism activities can have adverse impacts on these habitats, altering biodiversity and biocomplexity [ 155 ].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Tourism activities expanding into coastal areas, wetlands, coral reefs, and other sensitive ecosystems may lead to habitat degradation and loss [ 155 ]. Studies have revealed how infrastructure development, pollution from tourism activities, and physical disturbances due to tourism activities can have adverse impacts on these habitats, altering biodiversity and biocomplexity [ 155 ]. Tourism's impacts on water resources and aquatic ecosystems have long been documented, from solid waste generation and trash accumulation to degraded water quality [ 156 ].…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation